INOVASI TEKNOLOGI SEBAGAI SOLUSI UNTUK MENINGKATKAN WORK-LIFE BALANCE DAN KESEHATAN KERJA BURUH MIGRAN INDONESIA DI HONG KONG - Utaminingsih, Sri; Anwar, Saiful; Handayani, Estningsih Tri (Yayasan Education and Social Center, 2026)
Indonesian Migrant Workers (BMI) in Hong Kong, particularly those working in the domestic sector, face multidimensional challenges regarding work-life balance (WLB) and occupational health. Observations at the International Indonesia School Hong Kong (IISHK) reveal that many workers endure excessive working hours, reaching up to 21 hours per day, compounded by a lack of private space and social isolation. These conditions lead to severe physical and psychological exhaustion. This community service activity aims to introduce simple technological innovations as a solution to empower migrant workers. The method employed was a participatory workshop via Zoom Meeting, focusing on digital literacy for health management and legal advocacy. The results showed a significant shift in participants' behavior; they began utilizing health tracking applications and digital reminders to manage rest periods effectively. Furthermore, the program successfully established a digital peer-support system, which reduced feelings of isolation and increased workers' self-confidence in negotiating their rights. Technology, in this context, serves not only as a communication tool but as a vital instrument for achieving WLB and ensuring the well-being of migrant workers.